2018
DOI: 10.1371/journal.pone.0193730
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the probability of introduction and spread of avian influenza (AI) virus in commercial Australian poultry operations using an expert opinion elicitation

Abstract: The objective of this study was to elicit experts’ opinions and gather estimates on the perceived probability of introduction and spread of avian influenza (AI) virus in the Australian broiler and layer industry. Using a modified Delphi method and a 4-step elicitation process, 11 experts were asked to give initial individual estimates for the various pathways and practices in the presented scenarios using a questionnaire. Following this, a workshop was conducted to present group averages of estimates and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…environmental conditions, climate, presence of wild animals, etc.) 16,23 . Based on these premises, the presence of segregated poultry companies should represent an effective obstacle to viral shedding and the obtained results partially confirm these evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…environmental conditions, climate, presence of wild animals, etc.) 16,23 . Based on these premises, the presence of segregated poultry companies should represent an effective obstacle to viral shedding and the obtained results partially confirm these evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the co-circulation of field and live attenuated vaccines could enhance the likelihood of recombination and the vaccine induced immunity could promote and/or guide viral evolution 8,9 . Biosecurity measures and the proper understanding of the factors influencing viral spread are thus of primary importance. The risk factors of virus introduction in a farm have been investigated in several studies, and include transport of live poultry, species and productive category, dominant winds 10,11 , sharing of personnel, fomites and means of transportation [12][13][14][15][16] . Other routes of transmission are summarized under the umbrella of 'contiguous spread' .…”
mentioning
confidence: 99%
“…In addition, input values were also obtained from scientific literature. An expert opinion workshop was also held to obtain input values that were largely unknown or undescribed in the scientific literature ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…The second round of estimates for each question for all experts was then combined using a weighting factor depending on their respective level of expertise relevant to each question, in a discrete distribution. More details on the expert elicitation process and the outcomes of the study can be found in the study by Singh et al ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Experts have estimated the probability of LPAI introduction to free range and conventional meat chicken and layer flocks by contact with wild birds directly and indirectly [17] without the benefit of objective data.…”
Section: Australia Is a Relatively Isolated Island Continent And Not mentioning
confidence: 99%